Get smart too (Holland : SKF Maintenance Products [production company], 1994)
Maintenance products for professional engineers - induction, heaters, electronic instruments, mechanical pullers, lubricants, hydraulic equipment and mechanical fitting tools
Copy available in DVD format
Keywords: Maintenance and repair